2007
DOI: 10.1007/s10995-007-0223-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact Of Pediatricians’ Perceived Self-Efficacy and Confidence on Violence Prevention Counseling: A National Study

Abstract: Objective-To measure impact of pediatricians' perceived self-efficacy and confidence on current practices and attitudes regarding four violence prevention (VP) topics (gun storage, gun removal, limiting exposure to media violence, discipline techniques) during health supervision for children ages 2-11.Methods-Random sample survey of American Academy of Pediatrics Fellows (n = 486; 53% response rate) providing health supervision for children ages 2-11. Participants surveyed about VP issues regarding: (1) curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…Second, our response rate was 41%. While this rate compares favorably with the response rate in a domestic violence screening survey (Parsons, Zaccaro, Wells, & Stoval, 1995) of obstetrician-gynecologists (15%), it is somewhat lower than our own mail survey (Lapidus et al, 2002) on the same topic (49%) and among a national sample of pediatricians (53%) regarding violence prevention counseling (Finch et al, 2008). A third limitation of our study is self-selection.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Second, our response rate was 41%. While this rate compares favorably with the response rate in a domestic violence screening survey (Parsons, Zaccaro, Wells, & Stoval, 1995) of obstetrician-gynecologists (15%), it is somewhat lower than our own mail survey (Lapidus et al, 2002) on the same topic (49%) and among a national sample of pediatricians (53%) regarding violence prevention counseling (Finch et al, 2008). A third limitation of our study is self-selection.…”
Section: Discussionmentioning
confidence: 48%
“…In one study, time and lack of specific training were barriers to discussing violence prevention topics (Sege, Hatmaker, De-Vos, Levin, & Spivak, 2006). In another study of AAP fellows, most pediatricians did not routinely discuss violence prevention issues during health supervision visits with parents and their 2-5 and 6-11 year olds (Finch et al, 2008). In this national study, pediatricians' self-efficacy was related to counseling practices and the authors concluded that boosting self-efficacy could improve counseling frequencies.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A survey of 573 internists revealed that 58 percent had never asked patients about gun ownership, and 77 percent had never counseled patients on risks of firearm-related injury or death [20]. Similarly, less than half of surveyed pediatricians reported regularly providing firearm safety screening or counseling [18,[25][26][27]. At the medical student level, 66 percent of 1,469 seniors across 16 schools reported counseling patients about firearm safety "never" or "rarely,", with only 4 percent reporting doing so "usually" or "always" [16].…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis of either current violence involvement (perpetration or victimization), or risk for future violence perpetration or injury is rarely made. Pediatricians do not feel comfortable dealing with violence issues with their patients [3,4]. The rate of diagnoses of assault injury and violence perpetration in 10 -21 year olds in the primary care setting was reported to be only .3% and .84%, respectively, much lower than expected compared with national youth self report [5].…”
mentioning
confidence: 95%